Increasing Access to Higher Education Through Open and Distance Learning: Empirical Findings From Mzuzu University, Malawi - Chawinga, Winner Dominic; Zozie, Paxton Andrew (International Review of Research in Open and Distributed Learning, 2016)
Slowly but surely, open and distance learning (ODL) programmes are being regarded as one of the most practical ways that universities across the world are increasingly adopting in order to increase access to university education. Likewise, Mzuzu University (MZUNI) set up the Centre for Open and Distance Learning (CODL) to oversee the running of these programmes in 2011. In this study, we adopted the Transactional Distance Theory (Moore, 1997) to investigate the modes of instructional systems, benefits or opportunities, and the challenges associated with the delivery of ODL programmes at MZUNI. By self-administering a questionnaire to 350 ODL students and 9 Heads of Department in the Faculty of Education whose programmes are offered through ODL, we found that instructions are mostly delivered to students through print-based instructional materials. The major benefits noted include increased access to quality higher education, affordable tuition fees, and flexibility in payment of fees. However, we established some challenges which need to be addressed by the University which include, delayed feedback of assignments and release of end of semester examination results, absence of information for courses of study, poor communication between the Centre and departments, and poor remuneration for lecturers.